Holistic health care: Schlebusch, L (ed) (1990) Clinical health psychology: A behavioural medicine perspective. Halfway House, Tvl: Southern Book Publishers. - Tollman, Shirley (PINS-Psychology in Society, 2026)
The publication of this the first South African text dealing with Clinical Health Psychology is well-timed in view of the changing health care delivery system emerging within a "new• South Africa. Professor Schlebusch's longstanding professional concerns with "whole-person” hospital care to replace the prevailing biomedical approach (which ignores the impact of psychological and social forces upon disease, illness, and the healing process), as well as the proper application of psychological expertise by the health care team are addressed extensively in this publication. For example, he writes: "Comprehensive health care involves both psychological and physical care, which are inseparable” (pxix). Furthermore, Schlebusch and Lasich point out that "Clinical health psychology, behavioural medicine and consultation-liaison psychiatry are intimately associated with the biopsychosocial approach to patient care, particularly in general hospitals and related settings, and have become well established in recent years in industrialized and developed countries" (p326). But South Africa does not conform to this designation. At the present time it is a country in turmoil, a land grappling with the consequences of its own history, populated by an unique and complex mosaic of people who live somewhere within the extremes of rural and industrialized development, and whose lives range between poverty and wealth, privilege and deprivation, and who have grown up within diverse environmental, cultural and sociopolitical systems. Clinical health psychology in South Africa has now to address itself to the specific requirements of all its people.